(untitled) (International Journal of Food and Nutritional Sciences, 2021)
T.S. Eliot’s The Waste Land is a landmark of modernist literature, encapsulating the fragmentation, disillusionment, and spiritual desolation of the early 20th century. Published in 1922, the poem reflects the profound cultural and existential crises following World War I, as traditional values and artistic conventions were challenged by the upheaval of modernity. Through its innovative structure, intertextual richness, and thematic depth, The Waste Land exemplifies the core tenets of modernism, serving both as a critique of contemporary society and as a complex exploration of renewal and transcendence. Eliot’s fragmented narrative structure mirrors the chaos of modern life, rejecting linearity in favor of a collage of disparate voices, images, and allusions. Divided into five sections, the poem moves across time and space, weaving together myth, religion, and literature to reflect the universality of human experience amid cultural disintegration. The use of intertextuality—drawing from texts like Dante’s Inferno, the Bible, and Eastern scriptures—underscores modernism’s interplay between tradition and innovation, while highlighting the elusiveness of coherence in a fragmented world.